(untitled) (Journal of The Colloquium for Information Systems Security Education, 2026)
Cybersecurity operations often involve repetitive tasks such as running Nmap scans, analyzing logs, and performing Open-Source Intelligence (OSINT) investigations. These processes are essential for maintaining security but consume time and resources that many small organizations cannot spare. While commercial automation platforms exist to reduce this workload, they are typically costly and inaccessible to businesses without dedicated IT staff. This paper investigates n8n, a self-hosted and low-cost workflow automation platform, as a practical alternative for cybersecurity automation. By integrating security tools and external large language models (LLMs) such as ChatGPT, Gemini, and Ollama, n8n can automate vulnerability scanning, assign severity ratings, and generate reports tailored to both technical and executive stakeholders. Experiments show that n8n workflows can effectively combine traditional scans with Artificial Intelligence (AI)-driven analysis to produce actionable outputs. Although limitations remain, including a steep learning curve and restrictions in the free tier, n8n demonstrates potential for broadening access to automation in cybersecurity. For small organizations, this approach provides a cost-effective way to strengthen security posture, while in academic contexts it provides a hands-on platform for teaching and experimenting with automation and AI in cybersecurity.